Glembuk, Strategi Politik dalam Rekrutmen Elite Penguasa di Desa Pulungansari Yogyakarta - Bambang Hudayana (Humaniora, 2011)
Credibility is the power resource of village elites in Java that has ability to find out influence to the people. However, village elites also still require glembuk as a strategy to generate credibility, or to make the people merely under their control even though without legitimacy. Glembuk is implemented through conducting political transaction between the elites and the peoples, the elites persuate and negosiate their interest, and offer a compensation in term of services, goods, money or something that is important, or valuable for the peoples. Elites become to rely more on glembuk in the contestation of rulling elite recruitment such as village staff (pamong) and headman (lurah) direct election because they have no sufficient credibility requirement. The winers are the elites enabling to produce glembuk that manipulate and show off their potential as the credible leaders.